An elegant defense : the extraordinary new science of the immune system : a tale in four lives - Richtel, Matt (William Morrow, an imprint of HarperCollinsPublishers, 2019)
"A groundbreaking narrative exploration of the human immune system--the key to human health and longevity--from the Pulitzer Prize-winning New York Times journalist and acclaimed author of A Deadly Wandering"--